A abrangência de sanções econômicas direcionadas: o crescente recurso a sanções, overcompliance e seus efeitos no direito à saúde e na desigualdade de gênero em países-alvo - Gonelli, Aline (2025)
The use of economic sanctions, a prominent foreign policy mechanism, has expanded in recent years, with increasingly widespread applications of “targeted” sanctions that progressively affect key sectors and institutions in target countries. Since the 2010s, the scope of sanctions has been broadened by the adoption of mechanisms and practices that extend their extraterritorial reach, such as secondary sanctions and “overcompliance,” characterized by the exceedingly cautious behavior of private actors in the face of stricter sanctions—particularly unilateral measures imposed by the United States, their main promoter, through the Office of Foreign Assets Control (OFAC). In this context, restrictions on the international economic system imposed by sanctions have made transactions with sanctioned jurisdictions increasingly challenging, leading to disruptions in supply chains—including essential goods—and to the disorganization of domestic markets, with significant adverse effects on populations in the targeted countries. This study aims to understand how contemporary economic sanctions regimes operate, emphasizing the significant role and leadership of the United States, as well as the impacts of these policies on target countries, especially since their intensification in the 2010s. To illustrate these dynamics, it examines the effects on healthcare systems, a particularly affected sector, and the role of sanctions in worsening gender inequality, an issue that remains overlooked by sanctioning entities